The Effect of Anesthesia on TGF-β Levels in Lung Tumor Patients Undergoing Bronchoscopy: A Literature Review - Johannas; Efrida; Basyar, Masrul; Darwin, Eryati (Jurnal Kesehatan Komunitas Indonesia, 2026)
Lung cancer remains the leading cause of cancer-related mortality worldwide, with persistently low survival rates. Bronchoscopy is an essential diagnostic procedure in patients with lung tumors and often requires anesthesia to improve comfort and procedural success. Emerging evidence suggests that anesthetic agents and techniques may influence tumor biology through modulation of immune responses and inflammatory mediators. Transforming Growth Factor-Beta (TGF-β) is a multifunctional cytokine involved in cell proliferation, differentiation, immune regulation, and extracellular matrix remodeling, and plays a critical role in cancer progression. This literature review aims to evaluate current evidence regarding the effects of anesthetic agents and techniques on TGF-β levels and their implications for tumor biology in patients with lung tumors undergoing bronchoscopy. A narrative literature review approach was used to analyze scientific publications exploring the relationship between anesthesia, immune modulation, cytokine alterations, and cancer progression, particularly focusing on inhalational and intravenous anesthetics. Surgical stress and anesthetic exposure can alter immune responses through activation of neuroendocrine pathways, leading to cytokine imbalance and immunosuppression. TGF-β exhibits dual roles in cancer, acting as a tumor suppressor in early stages and a tumor promoter in advanced stages. Inhalational anesthetics may enhance tumor progression, whereas intravenous anesthetics such as propofol may have immunomodulatory effects. Anesthetic techniques may influence tumor-related pathways, including TGF-β; however, evidence remains limited and inconsistent, requiring further well-designed studies.